Prospective validation of a risk score based on biological markers for predicting progression free survival in Binet stage A chronic lymphocytic leukemia patients: Results of the multicenter O‐CLL1‐GISL study. Issue 7 (18th April 2014) - Gentile, Massimo; Cutrona, Giovanna; Mosca, Laura; Matis, Serena; Fabris, Sonia; Lionetti, Marta; Ilariucci, Fiorella; Zupo, Simona; Musolino, Caterina; Levato, Luciano; Molica, Stefano; Di Raimondo, Francesco; et al.
<x xml:space="preserve">Abstract</x> A risk score based on three biological features (CD38, ZAP‐70, and IGHV mutational status) was previously developed to predict progression‐free survival (PFS) in untreated Binet A CLL patients. Here we perform a score validation analysis in a prospective and independent cohort of patients. Biological markers (CD38, ZAP‐70, and IGHV mutational status) and gene expression profiles (GEP) of leukemic cells from CLL patients included in a prospective multicenter observational study (O‐CLL1‐GISL protocol, clinicaltrial.gov ID:NCT00917549) were used to assess the value and reproducibility of this score. To date, 468 Binet A patients were classified as low‐ (0 positive marker), intermediate‐ (1 positive marker), or high‐risk (2 or 3 positive markers) using the progression risk score. The 3‐year PFS probability was 91.7%, 82.9%, and 57.4% for low‐, intermediate‐, and high‐risk (P < 0.0001) cases, respectively. These values were similar to those found in the original cohort. At Cox multivariate analysis, Rai stage, absolute lymphocyte count, progression risk score, and β‐2 microglobulin maintained an independent prognostic impact on PFS. This score remained a predictor of progression when analysis was limited to 371 Rai 0 cases (P < 0.0001). Finally, the cells from the different CLL risk groups showed differences in their gene expression patterns. These results confirm the ability of this progression risk score to predict PFS among Binet A patients. The utility of the score was also extended by demonstrating that it retains prognostic value when applied exclusively to Rai 0 patients. Specific transcriptional patterns were significantly associated with risk groups. Am. J. Hematol. 89:743–750, 2014. © 2014 Wiley Periodicals, Inc.